Analysis of the Effect of Working Capital Management and Leverage on Profitability of Automotive and Component Companies on the Indonesia Stock Exchange - Kasman Pandiangan; Pardomuan Sihombing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Industry or industrial business is a business unit (unit) that contains people who have responsibility for the business and carry out economic activities to produce goods or services. One of the fields in the industry is the manufacturing industry. The data is processed based on the financial statements of 12 companies which are included in the Automotive and component subsectors by calculating the Return on Assets. Working capital is needed in carrying out business activities. Every industry certainly requires working capital in carrying out daily operational activities. To support every activity contained in industry, of course, proper working capital is needed both in quality and quantity. The data analysis model used in this research is quantitative, namely using the multiple linear regression analysis methods. In regression analysis, in addition to measuring the strength of the relationship between two or more variables, it also shows the direction of the relationship between the dependent variable and the independent variable. to accept H2. This means that the average collection period partially has a negative and significant effect on profitability. This is due to the company's ability to accelerate the collection of receivables